A retrospective and prospective study of double malignancies in a tertiary care hospital in south India - a ten years’ experience - Joseph, S. Carbin; Darlington, C. Danny; Anitha, G. Fatima Shirly (International Surgery Journal, 2016)
Background:The occurrence of second malignancies in cancer survivors is not uncommon. Due to advances in diagnostic and therapeutic modalities, the survival of cancer patients has improved and the incidence of second malignancies is also on the rise. The second malignancy may be synchronous or metachronous. Though there are plenty of case reports on double malignancies, original studies are less. The present study aims to analyse the frequency, types of double malignancies and their effect on the morbidity and mortality of the patients. Methods: This is a retrospective and prospective analysis of cancer patients done in a tertiary care hospital. All patients who presented with double malignancies from January 2004 to December 2014 were included. Retrospective data was obtained for cases from January 2004 to October 2011 and prospective data was obtained from November 2011 to December 2014. The study included 32 patients with double malignancies. Results:Gynaecological malignancies were most common in our study, followed by head and neck and gastrointestinal malignancies. Most of the malignancies were synchronous (56.25%). Double malignancies involving the head and neck, female reproductive tract, breast can be explained by common etiological factors like Human papillomma virus (HPV). Field cancerisation explains the synchronous cancers in Head and neck, upper aero digestive tract and reproductive tract. Conclusions:This study emphasises the importance of screening cancer patients for other primary malignancies during initial evaluation as well as during follow up period, in addition to the metastatic workup. It also stresses that timely reduction of risk factors in cancer survivors can prevent further malignancies.